INNOVATIVE MARKETING RESEARCH TOOLS - BILYK, Viktoriia; PROTSENKO, Andrii; VOINIKOVA, Anna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The current stage of economic development is characterized by rapid transformations, intensified competition, and the comprehensive digitalization of business processes. Under these conditions, marketing research has acquired strategic importance as a key tool for making managerial decisions based on objective data. Accordingly, there is a growing need to implement innovative approaches that ensure the fast acquisition, accurate processing, and deep interpretation of market information. Traditional data collection methods — such as surveys, focus groups, and expert evaluations — are increasingly giving way to digital technologies that integrate Big Data, Artificial Intelligence (AI), Machine Learning, automated online surveys, and neuromarketing tools.The aim of the study is to systematize and scientifically substantiate innovative marketing research tools that can enhance the efficiency of analytical processes and the quality of managerial decision-making. The scientific novelty lies in identifying the transformation trends of marketing analytics in the digital economy and determining the synergy between traditional and innovative data analysis methods. Particular attention is paid to the use of artificial intelligence technologies for predicting consumer behavior, the implementation of automated data collection systems to minimize human error, and the role of neuromarketing in shaping emotionally driven strategies for influencing target audiences.The research results confirm that digital tools significantly improve forecasting accuracy, reduce data processing time, and increase business adaptability in uncertain environments. However, the effective use of these technologies requires an integrated approach — the combination of multiple data sources, ensuring information security, improving marketers’ digital literacy, and developing flexible analytical systems.The conclusions highlight that innovative marketing research tools are becoming a critical factor in the competitiveness of enterprises in the era of digital transformation. Further scientific development in this field should focus on creating adaptive data analysis models that combine the technological capabilities of artificial intelligence with the practical needs of marketing management.
Keywords: innovative tools; market research; digital technologies; artificial intelligence